2019
DOI: 10.1080/10942912.2019.1683027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bioactive chemical components and antioxidant activities in three tissues of six varieties of Citrus grandis ‘Tomentosa’ fruits

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Comparison of the bioactive chemical components and antioxidant activities in three tissues of six varieties of Citrus grandis 'Tomentosa' fruits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In total, 61 essential oil chemical components were identified and listed in (Table 1 ). The families of detected essential oils in leaves mainly included terpenes (48.41%) and the oxygen-containing derivatives of the terpenes-alcohols (34.73), which were consistent with the previous reports, but the contents were higher than those extracted from the Citri grandis Exocarpium (fruit) [ 19 , 20 ]. The major compound was β-caryophyllene (15.75%), followed by (3R,6E)-nerolidol (12.66%), bicyclogermacrene (10.74%), β-citronellol (5.21%), 1-Methyl-4-(1-methyl ethylidene)-2-(1-methylvinyl)-1-vinylcyclohexane (4.92%), geraniol (4.12%) and phytol (4.03%).…”
Section: Resultssupporting
confidence: 91%
“…In total, 61 essential oil chemical components were identified and listed in (Table 1 ). The families of detected essential oils in leaves mainly included terpenes (48.41%) and the oxygen-containing derivatives of the terpenes-alcohols (34.73), which were consistent with the previous reports, but the contents were higher than those extracted from the Citri grandis Exocarpium (fruit) [ 19 , 20 ]. The major compound was β-caryophyllene (15.75%), followed by (3R,6E)-nerolidol (12.66%), bicyclogermacrene (10.74%), β-citronellol (5.21%), 1-Methyl-4-(1-methyl ethylidene)-2-(1-methylvinyl)-1-vinylcyclohexane (4.92%), geraniol (4.12%) and phytol (4.03%).…”
Section: Resultssupporting
confidence: 91%
“…It has been used to treat respiratory diseases for hundreds of years ( Su et al., 2020 ). Recent studies have shown that ECG possess antioxidant, anticancer, antibacterial, and anti-inflammatory activities owing to its rich bioactive compound profile ( Fan et al., 2019 ; Peng et al., 2019 ; Liu et al, 2022 ). Duan et al (2014) examined the bioactive compound profile of different tissues of C. grandis and identified the presence of naringin and rhoifolin in the fruit and flower.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and efficacy of ECG for medicinal use is dependent on its bioactive compound profile, indicating that the adoption of methods for increasing the accumulation of secondary metabolites could improve ECG efficacy. An analysis of the appearance and secondary metabolites of the three main varieties of C. grandis revealed that the trichomes and flavonoids of the three varieties were different ( Fan et al, 2019 ; Tian, Fan & Zeng, 2021 ). Fan et al (2023) further screened 25 genes and 16 transcription regulatory factors related to flavonoid biosynthesis using metabolomics and transcriptomics, which may be involved in the biosynthesis of flavonoids in C. grandis ‘tomentosa’ fruit.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The content of bioavonoids varies in different plants, and even in different parts or different life cycle phases of the same plant. 7 Therefore, rapid, simple, and reliable detection of bioavonoids in such agricultural products is essential for daily food control, orchard management, and metabolomic studies. Separationbased analytical methods, such as high-performance liquid chromatography 8 and gas chromatograph, 9 are conventionally used for bioavonoid determination with high sensitivity; however, they require complex and expensive equipment operated by professional technicians.…”
Section: Introductionmentioning
confidence: 99%